2022
DOI: 10.3390/bdcc6010017
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Analytics in Supply Chain Management: A Systematic Literature Review and Research Directions

Abstract: Big data analytics has been successfully used for various business functions, such as accounting, marketing, supply chain, and operations. Currently, along with the recent development in machine learning and computing infrastructure, big data analytics in the supply chain are surging in importance. In light of the great interest and evolving nature of big data analytics in supply chains, this study conducts a systematic review of existing studies in big data analytics. This study presents a framework of a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 117 publications
(148 reference statements)
4
28
0
Order By: Relevance
“…The study's results confirmed that big data analytics capabilities have made a positive contribution to enhancing the green supply chain performance in the Jordanian food and beverages manufacturing firms sector. The study's results are in agreement with much literature (Benzidia et al, 2021;Lee and Mangalaraj, 2022;Mani et al, 2017;Pandey et al, 2021). Big data analytics can provide new and original insights that can be used to improve the response of the green supply chain to various changes (Hsu et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The study's results confirmed that big data analytics capabilities have made a positive contribution to enhancing the green supply chain performance in the Jordanian food and beverages manufacturing firms sector. The study's results are in agreement with much literature (Benzidia et al, 2021;Lee and Mangalaraj, 2022;Mani et al, 2017;Pandey et al, 2021). Big data analytics can provide new and original insights that can be used to improve the response of the green supply chain to various changes (Hsu et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…Studies showed the positive and direct impact of big data analytics capabilities on green innovation and green supply chain performance (Benzidia et al, 2021;Imran et al, 2021;Lee and Mangalaraj, 2022;Mani et al, 2017;Waqas et al, 2021;Yaoteng and Xin, 2022). The causal relationship between green innovation and green supply chain performance has also been established in much previous literature (Bag et al, 2022;Fernando et al, 2019; Rodr ıguez-Gonz alez et al, 2022).…”
Section: 4mentioning
confidence: 71%
See 2 more Smart Citations
“…Its main functions include (1) resource allocation and recovery; (2) resource scheduling and optimization; and (3) system energy consumption and control. Realize resource allocation on demand, dynamic scaling of source pool, resource synchronization control, and automatic adjustment of resource distribution [ 20 ].…”
Section: Intelligent Community Architecture Design Based On Iotmentioning
confidence: 99%